Hydrophobicity in catalysts for wet peroxide oxidation - Martin-Martinez, Maria (2015)
Organic pollutants, such as phenol and its derivatives, are commonly present in wastewaters from several industries. These compounds are difficult to remove by conventional biological processes, mainly when present at high concentrations (1-10 g L-1)1. Catalytic wet peroxide oxidation (CWPO) is regarded as a potential solution for the treatment of aqueous effluents containing this type of recalcitrant, toxic and non-biodegradable compounds.